The Impact of Marketing Mix Elements on Tourist's Satisfaction towards Five Stars Hotel Services in Dubai during COVID-19 - JAHMANI, Ashraf; JAWABREH, Omar; ABOKHOZA, Reneh; ALRABEI, Ali Mahmoud (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023DO - 10.14505/jemt.v14.2(66).04, 2023)
Purpose: Tourist satisfaction measures the prosperity of a business and tourism sector. If there are many satisfied tourists, the tourism sector will profit, but if there are many less satisfied tourists, the tourism sector will lose money. Therefore, it is necessary to know the factors that affect tourist satisfaction. This study aims to develop and implement a method for five-star hotels to identify attributes that will increase tourists' satisfaction during the pandemic. Method: The study used 100 tourists in Dubai as respondents who were selected randomly at five-star hotels. The results showed no impact of all marketing mix elements on tourist satisfaction except the physical evidence of the COVID-19 pandemic. Outcomes: The results of this study indicated that the COVID-19 pandemic influenced five-star hotel services in Dubai and that the marketing mix elements used by the hotels are an important factor in tourist satisfaction. In conclusion, Dubai must understand the importance of a marketing mix to fulfil tourist satisfaction and improve the service that makes it more significant in the tourism industry. Originality: Numerous modifying variables impacting the management process have been examined in the literature on complaint management. It is the first study investigating the five-star hotel in Dubai to check the operative services on how to work on tourist satisfaction and determine the impact of marketing mix elements on tourism during the pandemic.